Characteristics of Worship Music at HKBP Simpang Limun Medan Church - Ezra Susilawaty Pangaribuan; Mauly Purba; Pulumun Peterus Ginting (Gondang: Jurnal Seni dan Budaya, 2024)
This research discusses the characteristics of worship music at the HKBP Simpang Limun Church in Medan, focusing on the evolution of the presentation of worship music which has now shifted to contemporary music. This transformation can be clearly seen in the use of modern musical instruments such as keyboards, acoustic guitars, bass guitars, drums and saxophones which have replaced the monotony of a single organ in the presentation of worship music. These changes not only create a richer variety in musical expression, but also enrich the worship experience for the congregation, reflecting the church's adaptability in responding to changing times. The purpose of this research is to determine the characteristics of worship music at the HKBP Simpang Limun Church, Medan. The research was conducted at the HKBP Simpang Limun Medan church, Jl. Brother No.30 Sudirejo II, Medan City District, Medan, North Sumatra. The approach used in this research is qualitative with a descriptive type where data is collected using observation, interviews, documentation and literature study methods. Based on the research results, it can be seen the characteristics of the music used in worship at the HKBP Simpang Limun church in terms of style, genres, textual, composition, transmission, movement.